2020
DOI: 10.3390/molecules25184179
|View full text |Cite
|
Sign up to set email alerts
|

Mass and Heat Transfer of Thermochemical Fluids in a Fractured Porous Medium

Abstract: The desire to improve hydraulic fracture complexity has encouraged the use of thermochemical additives with fracturing fluids. These chemicals generate tremendous heat and pressure pulses upon reaction. This study developed a model of thermochemical fluids’ advection-reactive transport in hydraulic fractures to better understand thermochemical fluids’ penetration length and heat propagation distance along the fracture and into the surrounding porous media. These results will help optimize the design of this ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 37 publications
(38 reference statements)
0
1
0
Order By: Relevance
“…They conducted parallel core flooding experiments using high and low permeability carbonate rocks, and both rocks were stimulated efficiently due to the presence of TCF. Aljawad et al [ 50 ] showed that TCF could generate very high pressure and temperature through fractured reservoirs. They showed that TCF could be combined with hydraulic fracture treatments to create a complex fracture network to enhance the well productivity.…”
Section: Methodsmentioning
confidence: 99%
“…They conducted parallel core flooding experiments using high and low permeability carbonate rocks, and both rocks were stimulated efficiently due to the presence of TCF. Aljawad et al [ 50 ] showed that TCF could generate very high pressure and temperature through fractured reservoirs. They showed that TCF could be combined with hydraulic fracture treatments to create a complex fracture network to enhance the well productivity.…”
Section: Methodsmentioning
confidence: 99%